Identification of Ferroptosis-Related Prognostic Models and FDFT1 as a Potential Ferroptosis Driver in Colorectal Cancer - Duan, Lili; Cao, Lu; Liu, Jinqiang; Wang, Zixiang; Liang, Jie; Feng, Fan; Zhang, Jian; Hong, Liu; Zheng, Jianyong (Current Medicinal Chemistry, 2026)
AimsWe aimed to develop Ferroptosis-Related Gene (FRG) signatures to predict overall survival (OS) along with disease-free survival (DFS) in individuals with colorectal cancer (CRC).BackgroundPrediction of CRC prognosis is challenging. Ferroptosis constitutes a newly reported kind of cell death, and its association with CRC prognosis remains unexplored.ObjectiveThis research endeavored to establish a prognostic risk signature for colorectal cancer by leveraging ferroptosis-related genes (FRGs), with the objective of refining prognostic precision in clinical settings.MethodsThe clinical data and mRNA expression profiles were obtained from The Cancer Genome Atlas (TCGA) colorectal cancer cohorts. The Lasso algorithm was employed to develop the overall survival (OS) and disease-free survival (DFS) prediction models. These models were subsequently validated using independent data from GSE38832.ResultsOur research unveiled a significant difference in the expression levels of 85% of ferroptosis-related genes (FRGs) between CRC tissues and paracancer tissues. Out of these, 11 prognostic genes were pinpointed through univariate Cox analysis. By employing two models, patients were stratified into low- and high-risk groups based on predicted risk scores, which were subsequently validated as independent prognostic factors via multivariate Cox analysis. The robustness of these models was further confirmed through Receiver Operating Characteristic (ROC) curve analysis. Functional enrichment analysis indicated a predominance of cancer-associated pathways in the high-risk group, including WNT signaling, along with variations in immune status between the two risk categories. Leveraging the Connectivity Map (CMap) database, a total of sixteen potential therapeutic drugs were identified. Additionally, in vitro experiments corroborated that Farnesyl-Diphosphate Farnesyltransferase 1 (FDFT1) was underexpressed in CRC and exhibited tumor suppressive properties. More specifically, FDFT1 may augment ferroptosis in CRC by modulating the expression of the Iron-Sulfur Cluster Assembly Enzyme (ISCU).ConclusionOur study highlighted the significance of ferroptosis-related genes in the pathogenesis of CRC and underscored the potential of ferroptosis-related gene-based risk signatures as valuable tools for improving prognostic accuracy and tailoring therapeutic strategies. However, the validity of these predictive models required further validation through real-world studies to ensure their reliability and applicability.
Keywords: ferroptosis